DINAMIKA ATTRITIO-CONTRITIO DALAM MINGGU PERTAMA LATIHAN ROHANI ST. IGNATIUS LOYOLA - Popo, Frederick Ray (Sanata Dharma University, 2025)
Members of the Society of Jesus (Jesuits) are formed with a self-understanding as sinners loved by God. God’s love is the first and foremost impetus for transforming a sinner to repent. This self-image is cultivated through their formative experiences, particularly during the 30-day retreat based on the Spiritual Exercises (SE) of St. Ignatius of Loyola. This article presents the results of a literature-based study of the First Week of the SE. In this section, Ignatius guides retreatants to understand conversion as a dynamic transition from attritio to contritio. The meditative materials provided by Ignatius are intentionally designed to lead retreatants to a deep sense of horror and sorrow for their personal sins, while simultaneously reminding them that they are always loved by God. This approach is rooted in St. Ignatius’ own experience of conversion, especially during his time of ascetic practices in the town of Manresa between 1522 and 1523.